Penerapan Algoritma Backpropagation Dalam Memprediksi Jumlah Penduduk di Kecamatan Pematang Bandar Berdasarkan Nagori/Kelurahan - Meychael Adi Putra; Handrizal Handrizal; Jalaluddin Jalaluddin (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
The number of residents in a sub-district greatly influences the the welfare of the community in the sub-district. But to determine the population each year in the Subdistrict requires a considerable amount of time and with a relatively simple method. Therefore we need a study to predict the number of population in the coming year, the algorithm used is the Backpropagation algorithm, this algorithm aims to make a prediction process for the population in Pematang Bandar Subdistrict, North Sumatra. Based on the data obtained, the population in Pematang Bandar District has increased. This study uses 5 architectural models, namely 3-2-1, 3-4-1, 3-5-1, 3-6-1, 3-9-1. Of the five architectural models used, one of the best 3-4-1 architectural models was obtained with accuracy of 92.3%, epoch 796 iterations in 10 seconds and MSE 0,000930636. It is expected that the results of this study can contribute to the District in improving all aspects of community welfare in the future.